Population Change and Crime Change - Caulfield, Deborah (1982)
The relationship existing between population change and crime rates in the central city merits study. There is limited research in this area, and the vast majority of the literature focuses on the correlation between population density and crime in the Standard Metropolitan Statistical Areas (SMSA). These few studies explore various types of crime in relation to population density, rather than the investigation of the relationship between population change and crime rates in the central city